Improving Sesame (Sesamum indicum L.) Seed Yield through Selection under Infection of Fusarium oxysporum f. sp. sesami - Rasha Ezzat Mahdy; Dalia A. Gaber; Mohamed Hashem; Saad Alamri; Ezzat E. Mahdy (Plants, 2022)
Sesame (Sesamum indicum L.), the Queen of oilseeds, is infected with different pathogens, restricting its yield. Fusarium oxysporum f. sp. sesami is the most destructive disease of sesame worldwide, causing economic losses. This work aimed to develop new high-yielding strains, resistant and/or tolerant to Fusarium. Two cycles of pedigree selection were achieved under infection of Fusarium oxysporum f. sp. sesami. Two populations in the F2 (600 plants each) were used. The selection criteria were five single traits and another three restricted by yield. The restricted selection was better in preserving variability than the single trait selection. The observed genetic gain in percentage from the mid-parent in the F4-generation was significant for the eight selection criteria. Single trait selection proved to be an effective method for improving the selection criterion, but it caused deleterious effects on the other correlated traits in most cases. The seed yield increased by 30.67% and 20.31% from the better parent in the first and second populations, respectively. The infection% was significantly reduced by 24.04% in the first, and 9.3% in the second, population. The selection index improved seed yield, and its attributes can be recommended.